2012
DOI: 10.4306/pi.2012.9.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Do Child Abuse and Maltreatment Increase Risk of Schizophrenia?

Abstract: IntroductionIntroductionaaAlthough childhood abuse is a recognised risk factor for depression, post-traumatic stress disorder, and substance misuse, its role in the aetiology of psychotic disorder remained controversial. This is in part because the putative effect of childhood trauma on psychosis has been mostly evaluated by small, cross sectional, uncontrolled studies that raised methodological issues.MethodsPapers concerning the association between childhood trauma and psychotic disorders (to November, 2011)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 105 publications
2
43
0
4
Order By: Relevance
“…Both retrospective (Fisher et al, 2011) and prospective (Sideli et al, 2012) studies have demonstrated that individuals with psychotic illnesses had higher rates of traumatic early life events such as sexual abuse, but later life trauma has also been found to be correlated with the subsequent development of psychotic illnesses (Grubaugh, Zinzow, Paul, Egede, & Frueh, 2011). Some research has attributed gender differences in schizophrenia to a different psychological vulnerPsychosis 3 ability of men and women (Ammari, Heinrichs, & Miles, 2010_ENREF_75).…”
Section: Psychological Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both retrospective (Fisher et al, 2011) and prospective (Sideli et al, 2012) studies have demonstrated that individuals with psychotic illnesses had higher rates of traumatic early life events such as sexual abuse, but later life trauma has also been found to be correlated with the subsequent development of psychotic illnesses (Grubaugh, Zinzow, Paul, Egede, & Frueh, 2011). Some research has attributed gender differences in schizophrenia to a different psychological vulnerPsychosis 3 ability of men and women (Ammari, Heinrichs, & Miles, 2010_ENREF_75).…”
Section: Psychological Differencesmentioning
confidence: 99%
“…The biological, through epigenetic, neurodevelopmental, and endocrine action, affects the psychological and sociological; whilst psychosocial distress can have adverse effects on biological function (Read, Bentall, & Fosse, 2009), the development of mental illness generally and psychosis specifically (Bentall, Wickham, Shevlin, & Varese, 2012) through all life stages, from pre-and peri-natally, through childhood and early life adversity, to adulthood . Such stressors affect endocrine function, genetic expression of various neuronal proteins, and more macro cortical functioning: the principles of a complex relationship of genetic factors, neurodevelopment and psychosocial distress and trauma has garnered a significant and growing evidence base, with the precise interplay remains an area of active research (Sideli, Mule, La Barbera, & Murray, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chapman et al, 2004;Dube et al, 2003;McEwen, 2003;Rutter and Maughan, 1997;Teicher et al, 2002). Associations have been described for different diagnoses, including major depressive disorder (MDD; e.g., Kessler, 1997;Heim et al, 1997Heim et al, , 2004Teicher et al, 2006Teicher et al, , 2009Widom et al, 2007), borderline personality disorder (BPD; e.g., Crawford et al, 2009;Allen, 2008;Liotti et al, 2000;van der Kolk et al, 1994), anxiety disorders (e.g., Kessler et al, 1997) or schizophrenia spectrum disorders (overview Varese et al, 2012; see also Read and Bentall, 2010;Read et al, 2005;Rosenberg et al, 2007;Bebbington et al, 2004Bebbington et al, , 2011Betensky et al, 2009;Matheson et al, 2012;Sideli et al, 2012). Efforts to understand the impact of adverse experience on disorder have targeted developmental periods and type of experience.…”
Section: Introductionmentioning
confidence: 99%
“…This may vary with the 'dose' or intensity of experience, with different amounts of adversity cumulatively increasing the risk or predicting the onset of severe disorders (Rubino et al, 2009;Sugaya et al, 2012;Mueser et al, 2002). It may also vary with the definition of severe disorder: while increasing amounts of various adversities increase the risk in different disorders Read and Bentall, 2010), no dose effect was found for first-presentation psychosis patients (Fisher et al, 2010;Sideli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a narrative review of the evidence on child maltreatment and psychosis, published at about the same time as our meta-analysis, Sideli, Mule, La Barbera, and Murray (2012) caution that, "specificity of childhood abuse in psychotic disorders and, particularly, in schizophrenia has not been demonstrated" and go on to argue that, "So far none of the studies reported indicate that childhood abuse is either sufficient or necessary to develop a psychotic disorder. "…”
mentioning
confidence: 98%